Analisis Pengaruh AI ChatGPT Terhadap Minat Baca Mahasiswa Teknik Informatika di Universitas Pahlawan Tuanku Tambusai - Riski Aulia Risda; Raja Joko Musridho; Rian Eka Putra; Ahmad Reyhan Wahidi; Yuda Aidil Fitra; Okta Bernaldi (Journal on Pustaka Cendekia Informatika, 2024)
The development of artificial intelligence (AI) technology, especially ChatGPT, has brought significant changes in students' learning patterns. This study aims to analyze the effect of using ChatGPT on the reading interest of Informatics Engineering students at Pahlawan Tuanku Tambusai University. Using a descriptive qualitative approach, data was collected through observation, interviews, and documentation of active ChatGPT user students. The results of the study show that the majority of students are highly dependent on ChatGPT to complete academic assignments, which has an impact on decreasing interest in reading traditional learning resources such as textbooks and scientific journals. This dependence causes a decrease in students' critical thinking skills, analytical skills, and enthusiasm for independent learning. This phenomenon raises concerns about the quality of long-term learning, especially in fields that require logic and deep conceptual understanding such as Informatics Engineering. Therefore, it is necessary to strengthen digital literacy and direct the wise use of AI so that technology becomes a tool that strengthens, not replaces, the real learning process.